[(thf)5Ln(Ge9Si(SiMe3)3 - Klementyeva, Svetlana V.; Woern, Kevin; Schrenk, Claudio; Zhang, Minghui; Khusniyarov, Marat; Schnepf, Andreas (Inorganic Chemistry)
We report the synthesis of three neutral complexes with different coordination modes of a di-silylated metalloid germanium cluster to divalent lanthanides [(thf)5Ln(ηn-Ge9(Hyp)2)] (Ln = Yb (1, n = 1); Eu (2, n = 2, 3), Sm (3, n = 2, 3); Hyp = Si(SiMe3)3) by the salt metathesis of LnI2 with K2[Ge9(Hyp)2] in THF. The complexes were characterized by elemental analysis, nuclear magnetic resonance and UV-vis-NIR spectroscopy, and single-crystal X-ray diffraction. In thf solution, the formation of contact or solvate-separated ion pairs depending on the concentration is assumed. Compound 2 exhibits a blue luminescence typical for Eu2+. The solid-state magnetic measurements of compounds 2 and 3 confirm the presence of divalent europium and samarium, respectively.
CRIS-Team Scopus Importer:2023-04-14